Homologous recombination repairs secondary replication induced DNA double-strand breaks after ionizing radiation - Groth, Petra (Oxford University Press, 2012)
Ionizing radiation (IR) produces direct two-ended DNA double-strand breaks (DSBs) primarily repaired by non-homologous end joining (NHEJ). It is, however, well established that homologous recombination (HR) is induced and required for repair of a subset of DSBs formed following IR. Here, we find that HR induced by IR is drastically reduced when post-DNA damage replication is inhibited in mammalian cells. Both IR-induced RAD51 foci and HR events in the hprt gene are reduced in the presence of replication polymerase inhibitor aphidicolin (APH). Interestingly, we also detect reduced IR-induced toxicity in HR deficient cells when inhibiting post-DNA damage replication. When studying DSB formation following IR exposure, we find that apart from the direct DSBs the treatment also triggers formation of secondary DSBs peaking at 7–9 h after exposure. These secondary DSBs are restricted to newly replicated DNA and abolished by inhibiting post-DNA damage replication. Further, we find that IR-induced RAD51 foci are decreased by APH only in cells replicating at the time of IR exposure, suggesting distinct differences between IR-induced HR in S- and G2-phases of the cell cycle. Altogether, our data indicate that secondary replication-associated DSBs formed following exposure to IR are major substrates for IR-induced HR repair.